The Relationship Between Knowledge Level And Family Support On Medication Adherence In Patients With Diabetes Mellitus - Atthiyyah Nur Aini; Merry Tiyas A; Chamim Faizin (CV. Inara, 2026)
Background : Non-compliance in taking medication is the main determining factor that triggers the onset of complications in people with diabetes mellitus, so adherence to pharmacological therapy is a very important element in efforts to control this disease. The level of patient understanding related to diabetes mellitus and the support from the family are believed to have a significant role in encouraging increased patient adherence to the treatment regimen. The purpose of the research is to analyze the relationship between the level of knowledge and family support and medication adherence in patients with diabetes mellitus at the Kedungmundu Health Center, Semarang City. Method: This cross-sectional design observational analytical study involving 110 respondents of diabetes mellitus patients at the Kedungmundu Semarang Health Center was determined from a consecutive sampling technique based on inclusion and exclusion criteria. Data were collected using the Diabetes Knowledge Questionnaire (DKQ-24), Hensarling Diabetes Family Support Scale (HDFSS), Medication Adherence Report Scale (MARS-10), then analyzed with univariate and bivariate using the Spearman Rho test with a meaning of p<0.05. Results: The Spearman Rho test showed a positive correlation of Knowledge Level and Medication Compliance (p<0.05; r = 0.584). Positive correlation of Family Support and Medication Compliance (p<0.05; r = 0.503). Good knowledge level 61 respondents (55.5%), high family support 59 respondents (53.6%), high medication adherence 58 respondents (52.7%). Bivariate analysis showed that there was a significant positive correlation between the level of knowledge and family support for medication adherence to diabetes mellitus patients at the Kedungmundu Health Center in Semarang. Conclusion : The higher the level of knowledge and family support, the more compliant the medication the diabetic mellitus patients are.